Crescimento, endividamento e política fiscal : análise teórica e uma aplicação para a economia brasileira no período 1985-2005 - Rabelo, Tales Chenso da Silva (2008)
The present study analyzes the govemment's influence over the economies' growth rates. It is divided in 4 parts. At the first, eminently theoretical, a meticulous re-write of the formalization of the govemment activities in an autarchical economy with balanced budget is performed in line with Barro (1990) and Barro and Sala-i-Martin (1992). At the second, also theoretical, it is simulated the impact of a constrained tax burden (and/or debt capacity) over economies' growth rates in agreement with the model of Aizenman, Kletzer and Pinto (2007). The sequence of the work is predominantly empiric. After analyzed the effects of the debt and budget composition over the economies with the aid of Semmler and Greiner (2000) model; the research focuses on the evolution of the budget composition of Brazilian economy. Particularly, it is discussed the effect ofthe budget's bounds implicit on the 1988 constitution, and the rise on current expenses with a consequent reduction on the public infrastructure investments from 90's to now. This trade-off coincides with the set-up of Semmler and Greiner (2000) model, making possible simulations over the best options of fiscal policies from disturbances on the effective observed budget coefficients for Brazilian economy along the period 1991-2005. Particularly, it is discussed how a reduction on the govemment's consumption would increment the public infrastructure, increasing the economy potential product. Finally, in line with time series data for Brazilian economy over the period 19912005, it is estimated the structural parameters ofthe economy through the generalized method of moments. Nevertheless, it is analyzed the evolution of the Brazilian infrastructure composition over the period 1950-2005 emphasizing the reduction of public capital over the total capital stock in the economy. The research verifies that the reduction in the volume of public investments over the last two decades coincides with a significant reduction in the economy's growth rate.